Application of acupuncture therapy in relieving the anxiety among patients undergoing glaucoma surgery (针灸疗法缓解青光眼手术患者焦虑的效果观察) - LI Gonghui (李贡辉); (毛珍); MA Di (马迪); HUANG Chukai (黄楚开); TAN Ronghui (谭容慧) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of acupuncture therapy in relieving the anxiety of patients undergoing glaucoma surgery. Methods Totally 95 glaucoma patients undergoing trabeculectomy were randomly divided into two groups: control group with 47 cases and observation group with 48 cases. The perioperative health education was carried in both two groups 1 day before surgery. In the observation group, patients received acupuncture therapy 1 day and 30 minutes before surgery respectively. In the control group, patients were administrated with intramuscular injection of phenobarbital sodium 30 minutes before surgery. The Visual Analogue Scale for Anxiety (VAS-A) was used to measure the anxiety status of patient 1 day before surgery, 30 minutes before surgery, intraoperative period and 30 minutes after surgery. The non-invasive blood pressure and heart rate were measured. Results There was no significant difference in systolic pressure between two groups(P＞0. 05). A significant difference in diastolic pressure at 1 day before surgery was found between two groups(P＜0. 05). There was a significant difference in heart rate between two groups at 1 day before surgery, 30 minutes before surgery and 30 minutes after surgery, respectively (P＜0. 05). A significant difference was found in VAS-A score between two groups during intraoperative period and 30 minutes after surgery(P＜0. 05). Conclusion Acupuncture therapy shows a similar sedative and anti-anxiety effect as intramuscular injection of phenobarbital sodium among patients undergoing glaucoma surgery, moreover, avoiding the drug-induced adverse reactions and potential risks. (目的 探讨运用针灸疗法缓解青光眼手术患者焦虑的效果。方法 选取行小梁切除手术的95例青光眼患者为研究对象, 采用随机数字表法分成2组: 对照组47例和观察组48例。2组均在术前1天开展围手术期健康教育。观察组在术前1 d进行第一次针灸, 在手术前30 min进行第二次针灸治疗; 对照组仅在手术前30 min肌肉注射苯巴比妥钠。术前1天使用视觉模拟量表(VAS)评出基线焦虑分数, 测量患者的基线血压与心率, 此后在手术前30 min、术中、术后30 min使用VAS评估2组患者的焦虑水平, 测量患者的无创血压、心率。结果 术前1 d、术前30min、术中、术后30 min收缩压差异无统计学意义(P＞0. 05); 舒张压在术前1 d差异有统计学意义(P＜0. 05), 在术前30 min、术中、术后30 min差异均无统计学意义(P＞0. 05); 术中心率差异无统计学意义(P＞0. 05), 在术前1 d、术前30 min、术后30 min差异有统计学意义(P＜0. 05); VAS得分在术前1 d、术前30min差异无统计学意义(P＞0. 05), 在术中、术后30 min差异有统计学意义(P＜0. 05)。结论 术前应用针灸疗法可以达到苯巴比妥的镇静抗焦虑效果, 还能够避免因使用药物所带来的不良反应和潜在风险, 保证患者安全。)